The Role of Parents Education of Adolescents in Social Interaction in Aeknabara S-3 Village, Bilah Hulu District, Labuhanbatu Regency - Novika Febriana; Agus Anjar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to determine the role of parents in educating teenagers in social interaction. This study uses a qualitative approach with qualitative methods. The informants in this study were original parents who had teenage children aged 11-20 years in S-3 AekNabara Village, Bilah Hulu District, Labuhanbatu Regency, totaling 45 heads of families. Data was collected using the methods of observation, interviews, and documentation. Data analysis techniques to find out a description of the role of parents in educating teenagers in social interaction are given a number of questions where the data measurement technique uses open interviews. The results obtained in this study are: 1) Lack of parents in giving attention to children, 2) parents who must provide social needs for children such as taking time to gather together at home, 3) parents provide an understanding of the importance of social interaction both within the family and in the community, 4) parents who provide motivation about the importance of participating in activities -activities in the community in order to broaden the knowledge of teenagers. The results of the conclusions in this study areParents act as educators in the family so that their daily attitudes and actions provide a stimulus to children's behavior. Parents' mistakes in educating children can result in children in their development and difficulty adjusting to their environment. Family communication is good even though there is no special time and routine time to gather in the family where there is interaction and exchange of ideas between families, which can be discussed when family members gather. The role of parents motivates teenagers to participate in activities in the community.